2014
DOI: 10.1515/cclm-2014-0278
|View full text |Cite
|
Sign up to set email alerts
|

Practical experience using galectin-3 in heart failure

Abstract: Heart failure is a complex mechanical and neurohormonal syndrome where the left ventricle fails as a pump, resulting in stasis of blood in the lungs and the periphery resulting in the cardial features of effort intolerance, fatigue, and peripheral edema. As part of the neurohormonal and local mechanical strain, tissue macrophages resident in the myocardium secrete galectin-3 which is a paracrine and endocrine factor which stimulates additional macrophages, pericytes, myofibroblasts, and fibroblasts to prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…Out of 80 subjects enrolled, 30 patients (38%)—in accordance with a previous report based on the same method of Gal-3 assay in 101 AS patients undergoing transcatheter aortic valve implantation (TAVI) [21]—had a Gal-3 level higher than the cut-off value of 17.8 ng/mL, previously proposed for risk stratification in established HF [5,11]. …”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Out of 80 subjects enrolled, 30 patients (38%)—in accordance with a previous report based on the same method of Gal-3 assay in 101 AS patients undergoing transcatheter aortic valve implantation (TAVI) [21]—had a Gal-3 level higher than the cut-off value of 17.8 ng/mL, previously proposed for risk stratification in established HF [5,11]. …”
Section: Resultsmentioning
confidence: 85%
“…The predictive ability of Gal-3 was tested by comparing Kaplan–Meier survival curves by the log-rank test with Gal-3 levels categorized according to a cut-off value of 17.8 ng/mL, previously proposed for risk stratification in patients with established HF [5,11]. Deaths from any cause were considered as outcome events.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, several studies already showed that galectin-3 plays an important role in the development of different pathological conditions. Some studies proved that increased galectin-3 concentration is associated with high heart failure risk [17]. There are evidences that galectin-3 concentration increases signi cantly, both in chronic and acute heart failure, according to the progression of disease [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence convincingly suggest that the measurement of GAL-3 may be helpful in risk assessment of cardiac fibrosis and HF, both in the general population (28), and in patients with acute myocardial infarction (29).…”
Section: Gal-3mentioning
confidence: 99%